Evaluation of journal policies to increase promotion of transparency and openness in sport science research - Hansford, H. J.; Cashin, A. G.; Wewege, M. A.; Ferraro, M. C.; McAuley, J. H.; Jones, M. D. (Journal of Science and Medicine in Sport, 2022)
Increased transparency and openness of sport science research will improve the ability to appraise, replicate, and implement research findings. However, sport science journals need to support and prioritise practices that bolster transparency and openness to facilitate this. Journal policies that actively support transparency and openness have been shown to improve the quality, reproducibility and replicability of research. To date, over 1100 journals and funding agencies have ascribed to implementing one or more of the eight standards for transparent and open research described in the Transparency and Openness Promotion (TOP) Guidelines.